Conservation of Mass / Jenna Winterberg ; Illustrator : Timothy Bradley - Winterberg, Jenna; Bradley, Timothy (Huntington Beach, CA : Teacher Created Materials, 2016)
"You can't make something out of nothing. This is because there are certain laws that everything in the universe follows, including the conservation of mass. It may seem like magic, bit it's really a matter of matter."-- Provided by publisher.
Something out of nothing -- Physical changes -- Chemical changes -- Systems -- Energy matters -- History of the law -- Words to know -- Mysterious matter -- Think like a scientist.
Includes index
Grades 4 to 6
Keywords: Mass (Physics) -- Juvenile litersture; Relativity (Physic) -- Juvenile literature